The effect of return on assets and sales growth on financial distress in food and beverage companies listed on the indonesia stock exchange in 2019 – 2021 - Sri Liniarti; Rizky Surya Andhayani Nasution; Elina R. Gustarina (Institute of Computer Science (IOCS), 2024)
The purpose of this study is to determine the effect of Return on Assets (ROA), and sales growth in food and beverage sector companies for 3 (three) years, namely the 2019-2021 period. The population of this study is food and beverage sector companies that remain listed on the Indonesia Stock Exchange from 2019 to 2021 totaling 47 companies. Sampling was carried out by purposive sampling consisting of 21 companies. Using the SPSS program, research data were analyzed using a logistic regression analysis approach. This analysis shows that the ROA variable has a positive and significant effect on financial distress. Meanwhile, sales growth (SG) does not have a significant effect on financial distress.